2022
DOI: 10.3390/su14031724
|View full text |Cite
|
Sign up to set email alerts
|

E-Learning: Direct Effect of Student Learning Effectiveness and Engagement through Project-Based Learning, Team Cohesion, and Flipped Learning during the COVID-19 Pandemic

Abstract: The cross-impact of project-based learning, team cohesion, and flipped learning was investigated by examining their direct effects on student learning effectiveness, engagement, and engagement effects on learning effectiveness. The results of hypotheses testing were achieved using hierarchical regression analysis with SPSS-25 statistical packages for data analysis. The research model was empirically verified with quantitative data collected from 247 graduate/undergraduate business students based on their own e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 68 publications
0
36
1
3
Order By: Relevance
“…Moreover, the items related to students' motivation, use of English, and research skills were 11, 12, and 13, respectively. According to the analysis, it was highlighted that the youngest teachers (21)(22)(23)(24)(25)(26)(27)(28)(29)(30) reached the highest score (Table 5) since they strongly agreed with items 12 and 13, followed by the age group of 31-40, and then the 41-plus range. This finding was logical since the results demonstrated that younger teachers implemented CPBL more frequently when compared with older educators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the items related to students' motivation, use of English, and research skills were 11, 12, and 13, respectively. According to the analysis, it was highlighted that the youngest teachers (21)(22)(23)(24)(25)(26)(27)(28)(29)(30) reached the highest score (Table 5) since they strongly agreed with items 12 and 13, followed by the age group of 31-40, and then the 41-plus range. This finding was logical since the results demonstrated that younger teachers implemented CPBL more frequently when compared with older educators.…”
Section: Resultsmentioning
confidence: 99%
“…By sharing what they have learnt, students reinforce what they already know while also learning what they do not know. Because the project process is structured around an open-ended question initiated by the students, this will trigger their curiosity, captivate their attention, and keep them focused on its completion [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Multiple exposures to course materials can enhance students' achievement (Cheung, Li, Phusavat, Paoprasert, & Kwok, 2020). In addition, getting connected to distance education platforms contributes positively to students' learning achievement (Umar & Ko, 2022). In this regard, flipped learning presents similar advantages to computer-assisted learning, especially distance education.…”
Section: Discussionmentioning
confidence: 99%
“…One of the active learning and teaching methodologies that is gaining relevance in university settings is Team-Based Learning (TBL), which combines elements of the flipped classroom and collaborative work (Abio et al, 2019;Calimeris & Sauer, 2015;Guo et al, 2020;Oliván Blázquez et al, 2019;Swanson et al, 2019). As could be expected, this tendency has continued and expanded during the COVID-19 pandemic, although there are still few academic outcomes (Ahshan, 2021;Collado-Valero et al 2021;Umar & Ko, 2022).…”
Section: Introductionmentioning
confidence: 99%